Crescimento, morfologia e fisiologia do umbuzeiro sob diferentes concentrações de giberelina - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Fruticulture is one of the segments of the Brazilian economy that has been most prominent in the last years and continues in full evolution both with regard to the production of fresh fruits, as well as the industrialization of juices and nectars. The present study aimed to identify the effect of different concentrations of Giberelic Acid (GA3) on the initial growth of Spondias tuberosa and establish the adequate amount of GA3 for biomass increase. The work was carried out at the State University of Goiás, Câmpus Ipameri, Goiás. Spondias tuberosa 60 days old seedlings were transferred to 15-liter pots containing soil, sand and manure, at a ratio of 3: 1: 0.5, respectively. The experiment was carried out in full sunshine, following the completely randomized design with six treatments (at 300 days of age, the seedlings were treated with gibberellic acid at concentrations of 0, 150, 300, 450, 600 and 750 mg L-1) and five replicates, the plants were irrigated daily with water volume corresponding to the retention capacity of the substrate and determined by vessel mass. At 60 days after imposition of the treatments the plants were analyzed. The gibberellin accelerated the vegetative growth of the plants and allowed the formation of seedlings with robust root system and xylopodium, vigorous aerial part with greater number of leaves, leaf area and stem mass. The maximum accumulation of biomass in umbuzeiro seedlings occurred with application of 415 mg L-1 of GA3.
Keywords: Spondias tuberosa; Hormônio; Fruticultura; Caatinga; Endêmica; Spondias tuberosa; Plant regulator; Vegetative growth; Caatinga; Endemic; CIENCIAS AGRARIAS